Inovasi Pengolahan Tepung Keladi sebagai Alternatif Sumber Karbohidrat dalam Produk Pangan - Afria Nova (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2025)
Taro flour (Colocasia esculenta L. Schott) is a local food ingredient with significant potential to be developed as an alternative carbohydrate source. Its high starch content, dietary fiber, and functional properties make taro flour a promising candidate for use in various food formulations. Moreover, the widespread availability of taro in tropical regions supports its sustainable utilization. However, the development and application of taro flour face several challenges, such as high levels of antinutritional compounds (particularly oxalates), variability in characteristics among cultivars, limited processing technology, and low consumer acceptance. Therefore, innovation in processing techniques is needed, including pre-treatment methods to reduce antinutrient content, starch modification to enhance functionality, and composite formulation with other food ingredients to expand product applications. This article aims to establish a comprehensive conceptual framework for the innovative development of taro flour, focusing on processing technology, functional value, and commercialization potential. Through this approach, the development of taro-based products is expected to increase added value, support local food diversification, and strengthen national food security.